Uswatun Hasanah: The Excellence of the Prophet's Morals as a Foundation for Effective Da'wah from the Sirah Nabawiyah Perspective - Andaluzi, Fahmi (Jurnal Al-Hikmah: Jurnal Dakwah, 2023)
Morals are the core of Islamic teachings, the position of morals as a basis in religion has a strong urgency to be applied by every Muslim. In Islam, the Prophet is the main role model in this regard, his mission as a bearer of sharia and noble morals is a benchmark that must be followed. This paper seeks to discuss the morals and character found in the Prophet. In searching for data, the author fully uses the library research method by collecting data from various sources such as history books, hadith or scientific articles relevant to the discussion, the method used in this study is descriptive, namely the author only describes the discussion of the literature collected and researched in accordance with the themes and limitations studied. The results of this study indicate that the Prophet is the most noble of his character, the most noble of his character. The Prophet had all kinds of noble morals both vertically and horizontally, meaning that the Prophet was not only superior in noble characters applied to fellow creatures, the Prophet was also successful in conveying the teachings of Islam by applying praiseworthy morals. History records that since childhood he has been given privileges by Allah SWT, including the provision of praiseworthy morals and preservation from despicable traits. This noble character continues to increase along with the journey of life and preaching that is delivered, and the problems faced so that he reaches true moral perfection.